Penggunaan Media Kartu Pecahan untuk Meningkatkan Hasil Belajar Matematika Materi Pecahan Kelas 3 SD Ta’mirul Islam Inovatif - Komariah, Kokom Siti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This research is about Classroom Activity Research (PTK), this research is for students of Sd Ta'mirul Islam Surakarta. The numbers of the students are 26 students consists of 12 boys and 14 girls. Tje purpose of the research is to increase the result of learning  from the third grade of SD Ta'mirul Islam Surakarta by using fraction card media. The result of learning pre cycle with the standard of minimum criteria of mastery learning (kkm) 75 is got from the average class, it is 68,6. in the first cycle the average class score is 77,5. The number who is completed the learning is 19 students or 73%. In the second cycle the average class score is 81,1. The observation data shows the result of learning is increase. The number is 23 students or 88% are completed the learning, and who is not finished the learning is about 3 students or 12%. So the conclusion is the result of learning by using fraction card media can increase the score, activeness, and can motivate the students.